Gouty arthropathy: Review of clinico‐pathologic and imaging features. Issue 1 (5th October 2015) - Parathithasan, Nishanthinie; Lee, Wai‐Kit; Pianta, Marcus; Oon, Shereen; Perera, Warren
Summary: Gout is a common inflammatory arthropathy in adults, with the prevalence increasing in males of older age. It occurs when monosodium urate (MSU) crystals are deposited in joints and connective tissue causing inflammation. The gold standard for the diagnosis of gout is the demonstration of negatively birefringent, needle‐shaped MSU crystals through synovial fluid aspiration. However, this is an invasive technique and may not always be conclusive or feasible. Imaging techniques have been developed to aid in diagnosis of gout non‐invasively. Radiography has a low utility in the early diagnosis of gout and demonstrates erosions in late stages. Ultrasound (US) has a high overall sensitivity in diagnosing gout with the 'double contour' sign having a high specificity. Magnetic resonance imaging is good at detecting tophi, bone marrow oedema and erosions, but has a limited role in diagnosis because of its high cost and limited availability. Conventional computed tomography (CT) has no role in the routine diagnosis of gout before development of erosions and tophi. A newer technology, dual‐energy CT (DECT) has been shown to be able to detect MSU crystals burden with high accuracy. It has a higher specificity and lower sensitivity that US in gout diagnosis. However, because of radiation exposure and cost, it has a better utility in diagnosing clinically suspected gout complicated by other concurrent rheumatologic conditions or if radiography, US and synovial aspiration are inconclusive or not feasible. This paper will review the clinico‐pathologic and imaging features of gouty arthropathy.